Dendritic cell therapy for Type 1 diabetes suppression. (October 2012) - Giannoukakis, Nick; Trucco, Massimo
While dendritic cell-based therapy is a clinical reality for human malignancies, until now, some conceptual concerns have served to delay its consideration to treat human autoimmune diseases, even in light of almost two decades' worth of overwhelmingly supportive preclinical animal studies. This article provides an overview of the development of dendritic cell-based therapy for Type 1 diabetes mellitus, given that this is the best-studied autoimmune disorder and that there is a good understanding of the underlying immunology. This article also highlights data from the authors' pioneering Phase I clinical trial with tolerogenic dendritic cells, which hopes to motivate the clinical translation of other dendritic cell-based approaches, to one or more carefully selected Type 1 diabetic patient populations.